Kompetens på rätt plats? Upplevelser av en implementerad kompetensförsörjningsstrategi hos chefer inom Region Skåne - Söderlind,Lina; Borg,Lovisa; Bohman,Blenda (2025)
This qualitative study examined and evaluated managers’ experiences of an implemented competence supply strategy within the psychology services at Region Skåne and how it may have affected competence supply and competence development. The study was based on semi-structured interviews with nine managers at different organizational levels and was analyzed using a thematic analysis with an abductive approach. The results of the study demonstrated that the strategy might have contributed to a better utilization of competence among the specialized psychologists, a clarification of their roles and that the recruitment of new employees is perceived to be easier. However, some of the managers expressed uncertainty regarding the clarification of these roles, as well as if the strategy has contributed to reduced turnover of psychologists or if it is the impact of other factors. The results also presented a need for flexibility within the strategy to meet the organizational requirements and that it demands continuous evaluation. The study indicates that the competence supply strategy may encourage long-term organizational development and that an evaluation with other concerned parties, such as the specialist psychologists, can guide the strategy in the right direction
Keywords: Kompetensförsörjning; kompetensutveckling; HR-strategier; utvärdering; arbets- och organisationspsykologi; ledarskap; Competence supply; competence development; HR-strategy; evaluation; work and organizational psychology; leadership